5t+12=67

Simple and best practice solution for 5t+12=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t+12=67 equation:


Simplifying
5t + 12 = 67

Reorder the terms:
12 + 5t = 67

Solving
12 + 5t = 67

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 5t = 67 + -12

Combine like terms: 12 + -12 = 0
0 + 5t = 67 + -12
5t = 67 + -12

Combine like terms: 67 + -12 = 55
5t = 55

Divide each side by '5'.
t = 11

Simplifying
t = 11

See similar equations:

| -15=6p+15+10p | | 3-4(k+5)-2(6-3k)=5 | | 0.5b-9=4b+5 | | 3m+2=5m-7 | | 0.75x-7=86 | | 3(4x-1)=15-3x | | S-4=13 | | x^4-2x^3-5x^2-6x=0 | | 21=2x+3(2+x) | | .75x-7=86 | | 5x+10(2x-9)= | | 3x+1=0.5 | | -2.5e+6.7=-1.3 | | 5x=5x-5 | | -3+2h=-19 | | -4-(-2)=m(2-(-2)) | | 4-5(2-m)=0.5 | | -243=13y | | 2x+8+6x+5= | | 4(2X-1)-3=5(x-5) | | -4-(-2)=m(2+2) | | 12a+14a=8 | | 6r+2r=-23 | | 10h-9=32 | | 2x^2+2y^3-9xy-x=0 | | 3.2y+(-2.2)=-0.6 | | 16-(4m+3)=2+3m-17 | | (x+2)(x+2)=4(2x+3) | | y-5=3x-4 | | 2x^2+2y^3-9xy=x | | 6r+1+2r-23= | | -2q-63=49 |

Equations solver categories